The Level of Written Comprehension Skills of Orphaned Children in Relation to Some Other Variables A Field Study Conducted in Lattakia (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper aims at identifying the relation between the level of written comprehension skills and the "sex" variant in orphaned children, in addition to identifying the relation between the written comprehension skills and the orphanhood period. The study has been conducted in Lattakia Governorate, Syrian Arab Republic, particularly during the period between January and September of 2016, through which the researcher applies the descriptive method as it fits the type and purpose of the study. The researcher has arranged a test derived from the Writing activities for ages ranging from 9-10 years old in the standard curriculum in Syria. The targeted category involves all orphaned children within that range in Lattakia and it was carried out over 175 male and female children. This category has been chosen randomly. For the sake of the search, the researcher attempted to prove two presumptions and reach the following results: 1. For those Syrian orphaned children in Lattakia, there is no positive relation between their level of written comprehension and the sex variable. 2. For those Syrian orphaned children in Lattakia, there is no positive relation between their level of written comprehension level and the period of their orphanhood.